Novel Strategies to Reduce Pulmonary Hypertension in Infants With Bronchopulmonary Dysplasia - El-Saie, Ahmed; Shivanna, Binoy (Frontiers in Pediatrics, 2020)
Bronchopulmonary dysplasia (BPD) is a developmental lung disorder of preterm infants primarily caused by immature host defense mechanisms that prevent tissue injury and facilitate repair. This disorder is the most common complication of premature birth, and its incidence remains unchanged over the past few decades. Additionally, BPD increases long-term cardiopulmonary and neurodevelopmental morbidities of preterm infants. Pulmonary hypertension (PH) is a common morbidity of BPD. Importantly, the presence of PH increases both short- and long-term morbidities and mortality in BPD infants. Further, there are no curative therapies for this disease complex. Besides providing an overview of the pathogenesis and diagnosis of PH associated with BPD, we have attempted to comprehensively review and summarize the current literature on the interventions to prevent and/or mitigate BPD and PH in preclinical studies. Our goal is to provide insight to the therapies that have a high translational potential to meaningfully manage BPD patients with PH.